The Influence of Leadership and Motivation on Employee Performance at PT. Transplasindo Perkasa in Bandung - Kosasih Kosasih (Kontigensi : Jurnal Ilmiah Manajemen, 2019)
This study aims to determine the effect of leadership and motivation on employee performance at PT. Transplasindo Perkasa in Bandung. The method used is explanatory research with analytical techniques using statistical analysis with regression, correlation, determination, and hypothesis testing. The results of this study that leadership has a significant effect on employee performance by 44.9%, hypothesis testing is obtained t count > t table or (8.936 > 1.984). Motivation has a significant effect on employee performance by 40.6%; hypothesis testing is obtained t count > t table or (8,186 > 1,984). Leadership and motivation simultaneously have a significant effect on employee performance with the regression equation Y = 9.608 + 0.402X1 + 0.364X2 and the contribution of the influence is 54.0%, hypothesis testing is obtained F count > F table or (56.850 > 2,700).